The effects of whey protein fibrils on the linear and non-linear rheological properties of a gluten-free dough - Shan, Shengyue; Chen, Da; Federici, Enrico; Jones, Owen G.; Campanella, Osvaldo H. (Frontiers in Nutrition, 2022)
The increasing awareness of celiac disease, an autoimmune disorder caused by the consumption of products containing gluten, has led to a growing interest in the development of gluten-free bakery products. In this study, whey protein fibrils were incorporated to mimic the fibrous network of gluten. The rheological properties and microstructure of the developed gluten-free doughs were evaluated and compared with gluten doughs. Protein fibrils were prepared by heating a whey protein isolate (WPI) solution at 80℃ in an acidic environment with low salt concentration and then the fibril lengths were adjusted by leveling up the solution pH to 3.5 and 7. The dimensions of the fibrils were measured by Atomic Force Microscopy (AFM). Rice and potato starches were mixed with fibrils, WPI, gluten, or without protein, to form different doughs for further investigation. Shear tests, including stress sweep, frequency sweep, and creep recovery, were performed to study the viscoelastic properties of doughs under small or large deformation. The strain-hardening properties of doughs under biaxial extension were studied by the lubricated squeezing flow method. The microstructure of the doughs was characterized by Cryo Scanning Electron Microscopy (cryo-SEM). Compared with doughs prepared with WPI and no proteins, doughs incorporating fibril showed comparable linear viscoelasticity to gluten dough tested with stress sweep, frequency sweep, and creep recovery in the linear viscoelastic region. More differences between the protein fibril doughs were revealed in the properties rheological in the non-linear region. Creep recovery parameters such as compliance, elastic moduli during the creep and recovery stages of gluten dough were like those of WPF pH7 dough, but significantly different from those of the WPF pH3.5 dough. Strain hardening properties were found in the WPF pH7 dough, although not in WPF pH3.5 dough. Microstructural characterization showed that both fibrils prepared with the different conditions formed a continuous protein phase for the improvement of dough cohesiveness, but the structure of the phase was different between the two fibrils. To summarize, whey protein fibril at pH 7 seemed to have the potential of being used as an ingredient with similar functions to gluten in gluten free bakery products.